A comprehensive approach to the euro-area debt crisis: Background calculations - Zsolt Darvas; Christophe Gouardo; Jean Pisani-Ferry; André Sapir (Bruegel, 2011)
This background paper describes in detail the assumptions and calculations behind the results presented in Zsolt Darvas, Jean Pisani-Ferry and André Sapir 'A comprehensive approach to the euro-area debt crisis', Bruegel Policy Brief No 2011/02, February 2011. An assessment of the results and policy conclusions can be found in the Policy Brief.
Keywords: 330; Öffentliche Schulden; Staatsbankrott; Bankenregulierung; Haushaltskonsolidierung; Finanzpolitik; Wirtschaftspolitik; Griechenland; Irland; Portugal; Spanien